Analisis Strengths, Weaknesses, Opportunities, Threats Berdasarkan Indeks Maqashid Syariah (IMS) dalam Penegakan Hukum Ekonomi Syariah di Indonesia - Abdurrahman Hakim; Faisal Salistya; Abdul Husenudin (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the development of Sharia Economic Law (HES) in Indonesia using the Maqashid Syariah Index (IMS) approach. Although various previous studies have assessed the effectiveness of HES regulations and the performance of Islamic financial institutions, there is still a research gap in the limited use of IMS as a comprehensive measuring tool to systematically analyze aspects of policy and legal structure. IMS, which is based on the protection of religion, life, mind, descendants, and property, provides a more normative, integrative, and maqashid-based evaluative framework in assessing the quality of the implementation of Sharia-based economic law. This study uses a qualitative-descriptive method with a normative-juridical approach and content analysis of regulations, fatwas, court decisions, and performance reports of Islamic economic institutions. The SWOT analysis is compiled based on the results of the IMS value mapping using the parameters of tahdzib al-fard, iqamah al-‘adl, and jalb al-maslahah. The research findings indicate that the main strength of the HES lies in its strong regulatory support and maqasid framework, while its weakness stems from the low implementation of the Islamic Sharia Supervisory System (IMS) in supervision and policy. Opportunities arise from increasing sharia literacy, halal financial innovation, and national policy support. Threats include regulatory disharmony, digitalization challenges, and the low integration of the IMS in institutional performance evaluation. This research contributes to the refinement of Islamic economic law evaluation instruments and provides maqasid-based recommendations for strengthening regulations and policy implementation.